Penterjemahan pragmatik dalam konsep masa Arab-Melayu: satu analisis teori relevan - Jumingan, Muhammad Fauzi (Universiti Putra Malaysia Press, 2002)
Time is gold. Time is like a sword. Both these proverbs are used in Malay and Arabic culture for showing the significance of time. Unfortunately, the concept of time in Malay culture has been presented negatively. The Malay race is regarded as a ethnic group that not take care about the importance of punctuality. Is it true? This article will try to explain that problem by using a pragmatic analysis especially through Relevance Theory (TR). Based on the TR concept that engaged factors such as context, co-text, and intended meaning, TR is capable of solving the problem of this misconception in Malay culture. In this articles there are some data that are used to discuss some foreign lexical items that were assimilated in Malay vocabulary. Actually, the chosen lexical items were adapted and translated into the Malay language.